The Williams Love Affair With Pan - Johnson, Kim (Express)
This article comments on the late Dr. Eric Williams and his love and involvement in pan. Williams a well-known lecturer on politics and history loved Trinidad and Tobago's arts from early. Dr. Williams had enjoyed many years of mutual support with both the steelband movement and individual panmen, but their relationship had its ups and downs.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Popular music -- Social aspects -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago